Education-to-career pathways of international students in India - Goyal, Yashi; Chander, Subhash (Journal of International Students, 2026)
India’s expanding higher education sector is increasingly attracting international students. However, their education-to-career pathways remain underexplored. This study examines the influence of course selection, country of origin, gender, language proficiency, and sociocultural background on the mobility experiences, sense of belonging, and employability outcomes of international students in India. It draws on in-depth qualitative interviews with 30 students from diverse disciplines across three universities in Delhi, Pune, and Bengaluru. The research employs thematic analysis within a two-step framework of migration and acculturation/belonging. The findings reveal that while institutional expansion offers greater access, early barriers, including linguistic and cultural adjustments, limited employment rights, and uneven institutional support, hinder career integration. Informal networks, faculty mentorship, and culturally responsive pedagogies emerge as key mediators of adaptation, influencing decisions regarding settlement, return, or onward migration.